Reconstructing an ancient mining landscape: A multidisciplinary approach to copper mining at Skouriotissa, Cyprus - Kassianidou, Vasiliki; Agapiou, Athos; Manning, Sturt W. (My University, 2021)
Extensively worked in antiquity, Skouriotissa remains the only active copper mine on the island of Cyprus. The modern, open-cast operation, however, has almost completely obliterated the earlier mining landscape. Here the authors report the results of investigations, including dating, of the ancient topography of the mine. They incorporate spatial data derived from archival sources, recent fieldwork and absolute dating into a geographical information system to reconstruct the ancient mining landscape around Skouriotissa. Their approach holds promise for understanding other mining regions in Cyprus and beyond, by providing an example of how diverse source material can be used to reconstruct landscapes now destroyed or buried by open-cast mining operations.
Keywords: Cyprus; Skouriotissa; Ancient mining; Copper; Archaeometallurgy; GIS